Analisis Market Overreaction Sebelum Dan Sesudah Peristiwa Terorisme Di Indonesia - Anshar, M Chairul; Lutfi, Andi (Patria Artha Journal of Accounting dan Financial Reporting, 2020)
Investors in the capital market will react to terrorism incidents in Indonesia. Investors' reactions need to be observed to test the efficiency market hypothesis. This study aims to determine whether there is a market overreaction in LQ-45 companies in Indonesia before and after the terrorism incident. The test was carried out by taking LQ-45 company stock data one week before and one week after the terrorism incident. Company data is grouped into two categories, namely loser stocks and winner stocks. The selected sample is 40 companies indexed by LQ 45. The LQ 45 index is an index on the condition that the company is the top 60 companies with the highest market capitalization in the last 1-2 months. The sampling technique used purposive sampling. To test the research hypothesis, statistical analysis One sample T-test and Paired sample T-test were used. The results of this study indicate the influence of market overreaction before and after acts of terrorism.